Exceptional responses to pertuzumab, trastuzumab, and docetaxel in human epidermal growth factor receptor‐2 high expressing salivary duct carcinomas. Issue 12 (26th November 2018) - Park, Jong Chul; Ma, T. Martin; Rooper, Lisa; Hembrough, Todd; Foss, Robert D.; Schmitt, Nicole C.; Sawhney, Rishi; Flanders, Aaron; Kang, Hyunseok
Abstract : Background: Alterations in the human epidermal growth factor receptor‐2 (HER2) pathway have been identified in a subset of salivary duct carcinomas. Dual HER2 inhibition with trastuzumab and pertuzumab has superior antitumor efficacy to trastuzumab monotherapy in HER2‐positive breast cancer, yet its efficacy in HER2‐positive salivary duct carcinoma is unknown. Methods: We report 2 cases of exceptional responses of HER2‐positive salivary duct carcinomas to dual HER2 blockade and docetaxel combination and their molecular characteristics. Results: A 54‐year‐old man with recurrent metastatic HER2 expressing salivary duct carcinoma of the parotid gland after definitive concurrent chemoradiation achieved a complete response (CR) after 6 cycles of trastuzumab, pertuzumab, and docetaxel (TPH). A 42‐year‐old woman with HER2‐positive salivary duct carcinoma of the parotid gland with bone and liver metastases had CR with TPH and remains in remission on maintenance trastuzumab and pertuzumab. Conclusion: Dual HER2 blockage resulted in CR in patients with HER expressing salivary duct carcinoma and warrants further evaluation in this patient population.